Factors associated with academic-medicine faculty attrition before promotion to senior rank: A national-cohort study - Maria Pérez; William E. Freeman; Yaheng Lu; Donna B. Jeffe (PLOS One, 2026)
Background Women and certain groups remain underrepresented among academic-medicine faculty at senior ranks (associate professor or professor). Variables associated with attrition before promotion to senior rank remain understudied. Methods The Association of American Medical Colleges provided data for a national cohort of 129,860 U.S. MD-granting medical-school matriculants in academic years 1993–1994 through 2000–2001; the authors included graduates from 1997 through 2012, first appointed to full-time instructor or assistant professor between 2000 and 2020. Independent predictors of attrition before reaching senior rank (vs. retention, with or without promotion to senior rank) were identified using multivariable logistic regression analysis. Results Of 35,902 graduates appointed to instructor or assistant professor, 34,478 (96.0%) had complete data for analysis. Faculty were more likely to leave academic medicine before promotion to senior rank if they were female (vs. male), Asian, and underrepresented groups in medicine (each vs. White), had any (vs. no) debt, reported non-academic (vs. full-time faculty) career plans at graduation, were first appointed as instructor (vs. assistant professor), at institutions where tenure was unavailable (vs. not on tenure track), and in a Family Medicine or Psychiatry (vs. Medicine) department. Faculty were less likely to leave academic medicine before promotion to senior rank if they had at least one year (vs. no) research during residency, were first appointed at research-intensive (vs. non-research-intensive) institutions, in a Pediatrics or Surgery (vs. Medicine) department, and had received any (vs. no) research or other federal grants. Conclusion This national-cohort study contributes new knowledge to the literature about variables independently associated with academic-medicine attrition before promotion to senior rank, many of which are amenable to intervention. Programs that can foster students’ and trainees’ interest in academic-medicine careers, reduce debt, and promote grant-writing skills might reduce attrition before reaching senior rank and increase academic-medicine workforce diversity.